(untitled) (Географический вестник=Geographical bulletin, 2017)
Рассматриваются основные виды районирования водохранилищ, обсуждаются принципы выделения районов и проведения границ, предлагаемые разными авторами. Приводится районирование Нижне-Камского водохранилища с описанием таксонов. TO THE QUESTION OF DIVISION INTO DISTRICTS OF THE NIZHNE-KAMSKY WATER BASIN Principal views of division into districts of water basins, principles of allocation of areas and carrying out of borders, various authors are described. Division into districts of the Bottom-Kamsky water basin with the description taxon is resulted. K e y w o r d s: a water basin; division into districts; taxon; morphology; a morphometry.